Dual- versus single-agent HER2 inhibition and incidence of intracranial metastatic disease: a systematic review and meta-analysis - Anders Wilder Erickson (Nature Portfolio, 2021)
Abstract Observational studies have suggested that HER2 inhibition with trastuzumab may be associated with an increased incidence of intracranial metastatic disease (IMD) due to its ability to prolong survival. We hypothesized that prolonged survival associated with dual-agent HER2 inhibition may be associated with an even higher incidence of IMD. This study pooled estimates of IMD incidence and survival among patients with HER2-positive breast cancer receiving dual- versus single-agent HER2 targeted therapy, as well as trastuzumab versus chemotherapy, observation, or another HER2-targeted agent. We searched PubMed, EMBASE, and CENTRAL from inception to 25 March 2020. We included randomized controlled trials that reported IMD incidence for patients with HER2-positive breast cancer receiving trastuzumab as the experimental or control arm irrespective of disease stage. Among 465 records identified, 19 randomized controlled trials (32,572 patients) were included. Meta-analysis of four studies showed that dual HER2-targeted therapy was associated with improved overall survival (HR 0.76; 95% CI, 0.66–0.87) and progression-free survival (HR 0.77; 95% CI, 0.68–0.87) compared to single HER2-targeted therapy, but the risk of IMD was similar (RR 1.03; 95% CI, 0.83–1.27). Our study challenges the hypothesis that prolonged survival afforded by improved extracranial disease control is associated with increased IMD incidence.